An overview of heavily polluted landfill leachate treatment using food waste as an alternative and renewable source of activated carbon - Shehzad, A. (Institution of Chemical Engineers, 2015)
Landfill leachate is a complicated refractory wastewater which contains huge amount of organic compounds and ammonia. Recently, the adsorption technology exploiting on activated carbon has gained promising importance in the treatment of landfill leachate due to its simplicity in design and low preparation cost of activated carbon in addition to high treatment efficiency. In this study, the physical and chemical characterizations of fabricated activated carbon derived from renewable sources such as food waste were highlighted to shed a brighter understanding on their performance in removing pollutants from landfill leachate. The impacts of activating conditions, such as carbonization temperature, retention time and impregnation ratio were thoroughly studied and compared between conventional and microwave heating methods. The significance of the produced food waste derivative-based activated carbon is expected to contribute toward a sustainable environment by overcoming the ramification of landfill leachate menace particularly via the removal of non-biodegradable organic compounds. Conclusively, the expansion of food waste in the field of adsorption science represents a potentially viable and powerful tool, leading to superior improvement of pollution control and environmental conservation. Â© 2015 The Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.